ANALISIS PERSEPSI MASYARAKAT TERHADAP PERAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENGENDALIAN KEBAKARAN HUTAN (STUDI KASUS KARHUTLA DI DESA SALO KECAMATAN SALO KABUPATEN KAMPAR PROVINSI RIAU 2019) - Anggi Nabila Balqis; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the natural disaster of forest fires thatoccurred in the village of Salo subdistrict of Kampar District of Riau Province whichoccurred in 2019 even though there was already a (BPBD) tasked with controlling andpreventing natural disasters that occurred in Kampar district. In carrying out regionaldisaster management there are tasks that must be carried out by BPBD. Theformulation of the problem in this study is "What is the public perception of the role ofthe (BPBD) in the control of forest fires in Salo Village of Salo District of KamparRegency of Riau Province 2019". The purpose of this study is to find out the public'sperception of the role of the (BPBD) in the control of forest fires in Salo Village, SaloDistrict, Kampar Regency, Riau Province. This research method is qualitativedescriptive with data collection techniques through interviews consisting of 10questions and questionnaires consisting of 10 questions. The subjects in this study werethe entire salo village community of 2,060 heads of families. Determination ofpurposive sampling technique research sample with the number of samples as many as30 people of Salo village community. The result of this study is that public perception ofthe Regional Disaster Management Agency (BPBD) is very good. This is seen from theresults of the spread of questionnaires with the percentage of respondents' answers,which is 82% which proves that the Role of the Derah Disaster Management Agency(BPBD) in Forest Fire Control is very important. In line with the results of interviews to30 respondents who stated that the Role of the (BPBD) in Forest Fire Control iscurrently Very Good.Key Words : Community Perception, BPBD, Forest Fires.